PECULIARITIES OF APPLICATION OF DIGITAL TECHNOLOGIES IN ACCOUNTING AND TAXATION CONSULTING - Balaniuk, I.F.; Ivanyuk , T.L (The actual problems of regional economy development, 2022)
The article is aimed at studying the application of digital technologies in consulting on accounting and taxation, which are an important component of the development of accounting. It is determined that one of the promising areas of business development of enterprises is the introduction of digital technologies in their economic activity. It should be noted that the use of digital technologies is a very important issue for the activities of consulting companies for accounting and taxation. The influence of digital technologies on the development of consulting services in the field of accounting and taxation of business transactions is revealed. The aim of the article is to study the impact of digital technologies in accounting and taxation consulting in terms of the opportunities they create and the risks they pose. To achieve this goal, the article uses the following research methods, such as: deduction - to determine the main advantages and disadvantages of each type of digital technology; systems analysis - to study the accounting processes in their relationship and interdependence with the inclusion of causation; synthesis - to summarize the disparate aspects of digital technology research in accounting and taxation consulting; abstraction - to determine the generalized conclusions. The article analyzes in detail the types of digital technologies that can be used in accounting and taxation consulting; identified the main advantages and disadvantages of using digital technologies in the activities of consulting companies; the main features in the registration of business transactions during accounting and taxation by consulting companies using digital technologies are highlighted. The scientific novelty of the study is the systematization and analysis of digital technologies in accounting and taxation consulting, namely, six main information technologies are identified: cloud computing technologies; software robot and artificial intelligence technologies; blockchain technology; technologies for working with large data sets; The Internet of Things, as well as examples of the implementation of digital technologies in the field of accounting. The results of the scientific process can be used by consulting companies and business units in the accounting and taxation of third-party companies.